2014
DOI: 10.4141/cjas-2014-023
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 2: Identification and analysis of expression in calves’ urine during their first month of life

Abstract: Michałek, K., Dratwa-Chałupnik, A., Ciechanowicz, A. K. and Malinowski, E. 2014. Aquaporin 2: Identification and analysis of expression in calves’ urine during their first month of life. Can. J. Anim. Sci. 94: 653–659. Aquaporin 2 (AQP2) is a vasopressin-regulated water channel of the renal collecting duct and is excreted into urine. Renal excretion of AQP2 has been studied in humans, dogs, rats and mice. The aim of this study was to identify and analyze expression of AQP2 in calves’ urine. Short and controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…* P <0.05. shows the results of immunoblot analysis for uEV-AQP2. As reported previously for AQP2 in bovine samples [17], both glycosylated and non-glycosylated AQP2 were detected in the uEVs of cattle. Quantitative analysis showed that the levels of glycosylated, non-glycosylated and glycosylated + non-glycosylated (total) AQP2 were significantly decreased in the G group relative to the other two groups.…”
Section: Resultssupporting
confidence: 80%
“…* P <0.05. shows the results of immunoblot analysis for uEV-AQP2. As reported previously for AQP2 in bovine samples [17], both glycosylated and non-glycosylated AQP2 were detected in the uEVs of cattle. Quantitative analysis showed that the levels of glycosylated, non-glycosylated and glycosylated + non-glycosylated (total) AQP2 were significantly decreased in the G group relative to the other two groups.…”
Section: Resultssupporting
confidence: 80%
“…The apparent, exclusive accumulation of AQP2 Ser-261 in the apical plasma membrane observed in the tested calves allowed assuming that this protein, phosphorylated at this position, is most likely primarily involved in water transport to the interior of principal cells and is removed to urine by exocytosis. This could partially explain the increase in renal AQP2 excretion in calves observed in our previous studies with a simultaneous lack of the increase in blood plasma AVP concentration (Michałek et al, 2014a). As mentioned before, AVP-dependent increase in cAMP production and PKA activation are the main factors responsible for the phosphorylation of AQP2 at serine position 256.…”
Section: Discussionsupporting
confidence: 62%
“…In the absence of AVP stimulation, hypertonicity alone induced rapid plasma membrane AQP2 accumulation in rat kidney CCT (Hasler et al, 2008). Perhaps it is MAPK activation that is the main source of increased AQP2 accumulation in the apical membrane and its total excretion with urine in calves in response to additional water loss with faeces under osmotic diarrhoea (Michałek et al, 2014a). MAPK activation, which probably plays a significant role in the bovine kidney signalling cascade, may also explain the presence of AQP2 Ser-261 in the apical plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation